The Effect of Digitization of Jamsostek Mobile (Jmo) on The Satisfaction of Jht Claim Participants is Mediated by The Quality of Service at Bpjs Ketenagakerjaan Kendari Branch Office - Muhammad Wahyu Suleman; Ummy Kalsum; Ruslan Ruslan (Maneggio, 2025)
This study aims to examine: (1) the effect of Jamsostek Mobile (JMO) digitalization on the satisfaction of Old Age Security (JHT) claim participants at BPJS Ketenagakerjaan Kendari Branch Office; (2) the effect of JMO digitalization on service quality; (3) the effect of service quality on JHT claim participant satisfaction; and (4) the mediating role of service quality in the relationship between JMO digitalization and JHT claim participant satisfaction. This research employed a quantitative descriptive approach with Structural Equation Modelling (SEM) using Partial Least Squares (PLS). Data were collected through questionnaires from 104 participants who had submitted JHT claims via the JMO application. The findings reveal that: (1) JMO digitalization has a positive and significant effect on JHT claim participant satisfaction; (2) JMO digitalization has a positive and significant effect on service quality; (3) service quality has a positive and significant effect on JHT claim participant satisfaction; and (4) service quality mediates the effect of JMO digitalization on JHT claim participant satisfaction. These results highlight the strategic role of JMO digitalization in enhancing service delivery and customer satisfaction within BPJS Ketenagakerjaan.